Elektroniczna komunikacja pomiędzy stronami a sądem w europejskim postępowaniu w sprawie drobnych roszczeń – zagadnienia prawne i uwagi praktyczne - Klimas, Katarzyna (Wydawnictwo C.H. Beck, 2018)
The aim of this study is to analyze the legal and factual possibilities of implementing to the European model of small claims procedure electronic communication of parties with the court and electronic court activities, including the assessment of the scope of implementation of IT automatization, in European Small Claims procedure. Consideration in this respect begins with the verification of the legal basis laying under the provisions of EU and national law. Assessment of experiences related to the functioning of the Polish electronic writ-of-payment proceedings (EPU) provides the basis for an economic analysis of implementing electronic communication in the European Small Claims procedure and the impact of civil procedural rules on the implementation of the e-CODEX PLUS project assuming electronic communication in the European Small Claims Procedure and European Payment Order.
Keywords: European Small Claims Procedure; electronic payment order; electronic communication; electronic court activities